Planning a lab lesson on the law of thermal conduction with learning by preparing to teach design. (2nd October 2018) - Isik, Hakan; Alpaslan, Muhammet Mustafa
Abstract: Lab activities have been innovated and progressed to fulfill the purpose that students need to experience physics concepts through hands-on and minds-on interactions. However, student-centered and conceptual activities in physics labs are challenged with time and material constraints that degrades the merits of the learning environment. This study adopts a pedagogical design, "learning by preparing to teach", to address the challenges with conducting a satisfactory number of activities in physics labs and therefore promoting student hands-on and minds-on experiences with the activities. Eight activities covering the conceptual variables of thermal conduction in a two-hour lab session were studied by freshmen students at a university. To implement the pedagogical design, the students were arranged into the learning and teaching groups that paved way to a lab design that student was first learners and then teachers. Lab activities were configured that each group studied a certain set of activities. Upon completing the activities, members of the learning groups were designated to the teaching groups in which students cooperated to achieve conceptual objectives of the lab. The results showed that a usual lab duration becomes effective to cover numerous activities.